Influence of family planning and immunization services integration on contraceptive use and family planning information and knowledge among clients: A cross-sectional analysis in urban Nigeria - Kate L. Sheahan; Ilene Speizer; Siân Curtis; Morris Weinberger; John Paul; Antonia V. Bennett (Frontiers Media S.A., 2022)
Reproductive autonomy necessitates that women have access to high quality family planning information and services. Additionally, closely spaced pregnancies increase maternal and infant morbidity and mortality. Although integrating family planning into child immunization services may increase access to information and services and postpartum contraceptive use, evidence on how integration affects service delivery and health outcomes is scarce. One limitation of previous studies is the use of binary integration measures. To address this limitation, this study applied Provider and Facility Integration Index scores to estimate associations between integration and contraceptive use, receipt of family planning information, and knowledge of family planning services availability. This study leveraged pooled cross-sectional health facility client exit interview data collected from 2,535 women in Nigeria. Provider and Facility Integration Index scores were calculated (0-10, 0 = low, 10 = high) for each facility (N = 94). The Provider Integration Index score measures provider skills and practices that support integrated service delivery; the Facility Integration Index score measures facility norms that support integrated service delivery. Logistic regression models identified associations between Provider and Facility Integration Index scores and (a) contraceptive use among postpartum women, (b) receipt of family planning information during immunization visits, and (c) correct identification of family planning service availability. Overall, 46% of women were using any method of contraception, 51% received family planning information during the immunization appointment, and 83% correctly identified family planning service availability at the facility. Mean Provider and Facility Integration Index scores were 6.46 (SD = 0.21) and 7.27 (SD = 0.18), respectively. Provider and Facility Integration Index scores were not significantly associated with postpartum contraceptive use. Facility Integration Index scores were negatively associated with receipt of family planning information. Provider Integration Index scores were positively associated with correct identification of family planning service availability. Our results challenge the position that integration provides a clear path to improved outcomes. The presence of facility and provider attributes that support integration may not result in the delivery of integrated care.